Updated Characterization of Post‐OPV Cessation Risks: Lessons from 2019 Serotype 2 Outbreaks and Implications for the Probability of OPV Restart. Issue 2 (6th July 2020) - Kalkowska, Dominika A.; Pallansch, Mark A.; Cochi, Stephen L.; Kovacs, Stephanie D.; Wassilak, Steven G. F.; Thompson, Kimberly M.
Abstract: After the globally coordinated cessation of any serotype of oral poliovirus vaccine (OPV), some risks remain from undetected, existing homotypic OPV‐related transmission and/or restarting transmission due to several possible reintroduction risks. The Global Polio Eradication Initiative (GPEI) coordinated global cessation of serotype 2‐containing OPV (OPV2) in 2016. Following OPV2 cessation, the GPEI and countries implemented activities to withdraw all the remaining trivalent OPV, which contains all three poliovirus serotypes (i.e., 1, 2, and 3), from the supply chain and replace it with bivalent OPV (containing only serotypes 1 and 3). However, as of early 2020, monovalent OPV2 use for outbreak response continues in many countries. In addition, outbreaks observed in 2019 demonstrated evidence of different types of risks than previously modeled. We briefly review the 2019 epidemiological experience with serotype 2 live poliovirus outbreaks and propose a new risk for unexpected OPV introduction for inclusion in global modeling of OPV cessation. Using an updated model of global poliovirus transmission and OPV evolution with and without consideration of this new risk, we explore the implications of the current global situation with respect to the likely need to restart preventive use of OPV2 in OPV‐using countries. Simulation results without this new risk suggest OPV2 restart will likely need to occur (81% of 100 iterations) to manage the polio endgame based on the GPEI performance to date with existing vaccine tools, and with the new risk of unexpected OPV introduction the expected OPV2 restart probability increases to 89%. Contingency planning requires new OPV2 bulk production, including genetically stabilized OPV2 strains.